Role of information science in a complex society - Silva, Elaine da [UNESP]; Valentim, Marta Lígia Pomim [UNESP] (IGI Global, 2021)
The field of Information Science is intertwined with the complexity present in society. The study object in this field refers to data, information, and knowledge generated, mediated, and appropriated by different individuals in the most diverse human activities. Thus, discussing complex issues that are intertwined with information management, knowledge management, innovation management, organizational intelligence, information mediation, information appropriation, and information literacy is essential for understanding the future perspectives of digital humanity. Role of Information Science in a Complex Society presents discussions that can be applied to local, regional, and national policies aimed at economic and social development and supports innovative actions in economic segments that depend on innovation. Highlighting topics that include information literacy, ethics, knowledge management, and organizational learning, this book is an ideal reference source for academicians, professionals, researchers, and students, as well as entrepreneurs from different economic segments.